Wounded Lions : Joe Paterno, Jerry Sandusky, and the Crises in Penn State Athletics - Smith, Ronald A. (Ronald Austin), 1936- (Book collections on Project MUSE., 2016)
A rogue program, an iconic coach, and an unspeakable tragedy.